2020
DOI: 10.1063/5.0011229
|View full text |Cite
|
Sign up to set email alerts
|

Sensing of explosive vapor by hybrid perovskites: Effect of dimensionality

Abstract: Lead halide perovskites are very promising materials for many optoelectronic devices. They are low cost, photostable, and strongly photoluminescent materials, but so far have been little studied for sensing. In this article, we explore hybrid perovskites as sensors for explosive vapor. We tune the dimensionality of perovskite films in order to modify their exciton binding energy and film morphology and explore the effect on sensing response. We find that tuning from the 3D to the 0D regime increases the PL que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Moreover, the selectivity of CsPbBr 3 QDs to picric acid depends upon the hydroxyl group and nitro group. [60] Harwell et al [61] studied the effect of dimensionality on the fluorescent sensing of dinitrotoluene (DNT). Bulk CsPbBr 3 (3D), layered phenethylammonium based (PEA) 2 Cs 2 Pb 3 Br 10 (2D) and CsPbBr 3 NCs (0D) were used for DNT sensing.…”
Section: Nitrophenol Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the selectivity of CsPbBr 3 QDs to picric acid depends upon the hydroxyl group and nitro group. [60] Harwell et al [61] studied the effect of dimensionality on the fluorescent sensing of dinitrotoluene (DNT). Bulk CsPbBr 3 (3D), layered phenethylammonium based (PEA) 2 Cs 2 Pb 3 Br 10 (2D) and CsPbBr 3 NCs (0D) were used for DNT sensing.…”
Section: Nitrophenol Sensingmentioning
confidence: 99%
“…This enhanced effect is due to the higher vapor pressure of DNT compared to other landmine explosives. [61] Recently, Deng e al. [62] employed the super hydrophobic porous organic polymer framework (SHFW) protected CsPbBr 3 QDs (CsPbBr 3 @SHFW) to detect o-nitrophenol in dichloromethane.…”
Section: Nitrophenol Sensingmentioning
confidence: 99%
“…The effect of the dimensionality of the sensing material has instead been analyzed by Harwell et al [ 108 ], evidencing how by tuning the perovskite dimensionality from 3D (bulk ) to 2D (layered phenethylammonium ) and finally to 0D ( nanocrystals) structures can dramatically enhance the response of the films to external stimuli. nanocrystals ( Figure 24 c), thanks to their low dimensionality, have a high surface to volume ratio, which makes them efficient for the detection of 2,4-dinitrotoluene (DNT) vapors through photoluminescence quenching.…”
Section: Sensing Application Of Perovskitesmentioning
confidence: 99%
“…Moreover, the deposition process can change the morphology properties of the resulting film (such as the thickness and the substrate coverage) [ 49 , 66 ] affecting, in turn, the device sensitivity. Additionally, the dimensionality of the perovskite can strongly influence the response of the device and it has been shown that switching from 3D to 0D structures allows one to obtain an higher sensitivity to the external stimuli thanks to the 0D greater surface to volume ratio [ 108 ].…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation